2015
DOI: 10.1152/japplphysiol.00066.2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined resistance training and healthy diet on muscle mass in healthy elderly women: a randomized controlled trial

Abstract: The delivery of efficient nonpharmacological treatment to prevent the loss of muscle mass in older adults is a major challenge, and information on the combined effects of training and diet is particularly important. Here we aimed to evaluate the effects of 24 wk of resistance training combined with a healthy dietary approach (n-6/n-3 ratio < 2) in a population of healthy and physically active older women (65-70 years). The three-armed randomized controlled trial included a resistance training + healthy diet gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 63 publications
2
69
0
1
Order By: Relevance
“…These changes remained within the relative protein consumption guidelines for physically active individuals (Beasley et al 2016;Thomas et al 2016). The CC group also engaged in resistance training, which is also associated with the maintenance of lean body mass (Strandberg et al 2015). Given the CC groups maintenance of lean body mass throughout the study, this amount of protein coupled with a resistance training stimulus may have been sufficient to prevent an attenuation in lean mass.…”
Section: Discussionmentioning
confidence: 67%
“…These changes remained within the relative protein consumption guidelines for physically active individuals (Beasley et al 2016;Thomas et al 2016). The CC group also engaged in resistance training, which is also associated with the maintenance of lean body mass (Strandberg et al 2015). Given the CC groups maintenance of lean body mass throughout the study, this amount of protein coupled with a resistance training stimulus may have been sufficient to prevent an attenuation in lean mass.…”
Section: Discussionmentioning
confidence: 67%
“…The narrow age range was selected as part of inclusion criteria to a randomized controlled trial previously reported elsewhere [17]. All women were living in an urban area in Sweden and of white European origin.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of nonpharmacological strategies (diet or physical activity) in preventing SMM loss or treating sarcopenia are encouraging [25, 32, 33]. However, it is not known whether this reduces the health care burden and its expenditure.…”
Section: Introductionmentioning
confidence: 99%